Margin of Interest : On English Language Poetry of the Maritimes. - Neilson, Shane (The Porcupine's Quill, 2019)
The essays in Margin of Interest showcase the rich history of poetry in the Canadian Maritimes, recognizing the drawbacks of regional frameworks while finding power and beauty in the literary traditions of writers who exist on the margins of Canadian poetry and culture.